Metabolic Score for Visceral Fat (METS-VF), a novel estimator of intra-abdominal fat content and cardio-metabolic health. Issue 5 (May 2020) - Bello-Chavolla, Omar Yaxmehen; Antonio-Villa, Neftali Eduardo; Vargas-Vázquez, Arsenio; Viveros-Ruiz, Tannia Leticia; Almeda-Valdes, Paloma; Gomez-Velasco, Donaji; Mehta, Roopa; Elias-López, Daniel; Cruz-Bautista, Ivette; Roldán-Valadez, Ernesto; Martagón, Alexandro J.; Aguilar-Salinas, Carlos A.
Summary: Background & aims: Intra-abdominal and visceral fat (VAT) are risk factors for the development of cardio-metabolic comorbidities; however its clinical assessment is limited by technology and required expertise for its assessment. We aimed to develop a novel score (METS-VF) to estimate VAT by combining the non-insulin-based METS-IR index, waist-height ratio (WHtr), age and sex. Methods: We developed METS-VF in a sample of 366 individuals with Dual X-ray absorptiometry (DXA). METS-VF was modeled using non-linear regression and validated in two replication cohorts with DXA (n = 184, with n = 118 who also had MRI) and bio-electrical impedance (n = 991). We also assessed METS-VF to predict incident type 2 diabetes (T2D) and arterial hypertension independent of body-mass index (BMI) in our Metabolic Syndrome Cohort (n = 6144). Results: We defined METS-VF as: 4.466 + 0.011*(Ln(METS-IR)) 3 + 3.239*(Ln(WHtr)) 3 + 0.319*(Sex) + 0.594*(Ln(Age)). METS-VF showed better performance compared to other VAT surrogates using either DXA (AUC 0.896 95% CI 0.847–0.945) or MRI (AUC 0.842 95% CI 0.771–0.913) as gold standards. We identified a METS-VF cut-off point >7.18 in healthy patients which has 100% sensitivity (95% CI 76.8–100) and 87.2% specificity (95% CI 79.1–93.0) to identify increased VAT (>100 cm 2 ). METS-VF also had adequate performance in subjects with metabolically-healthy obesity. Finally, in our metabolic syndrome cohort, subjects in the upper quintiles of METS-VF (>7.2) had 3.8 and 2.0-fold higher risk of incident T2D and hypertension, respectively (p < 0.001). This effect was independent of BMI for both outcomes. Conclusion: METS-VF is a novel surrogate to estimate VAT, which has better performance compared to other surrogate VAT indexes and is predictive of incident T2D and hypertension. METS-VF could be a useful tool to assess cardio-metabolic risk in primary care practice and research settings. Highlights: We developed a novel estimator of visceral and intra-abdominal fat. METS-VF was validated against DXA, MRI and BIA and outperforms competing models. Adverse adipokine profiles correlate with higher METS-VF values. METS-VF predicts incident type 2 diabetes and hypertension independent of BMI. METS-VF is a novel estimator of cardio-metabolic health.